Regulation of MYCN expression in human neuroblastoma cells - de Vries I; Hulsbergen-van de Kaa Christina A; van Leeuwen Frank N; van Bokhoven Hans; Jacobs Joannes FM; Adema Gosse J; Hoogerbrugge Peter M; de Brouwer Arjan PM (BMC Cancer, 2009)
Abstract Background Amplification of the MYCN gene in neuroblastoma (NB) is associated with a poor prognosis. However, MYCN-amplification does not automatically result in higher expression of MYCN in children with NB. We hypothesized that the discrepancy between MYCN gene expression and prognosis in these children might be explained by the expression of either MYCN-opposite strand (MYCNOS) or the shortened MYCN-isoform (ΔMYCN) that was recently identified in fetal tissues. Both MYCNOS and ΔMYCN are potential inhibitors of MYCN either at the mRNA or at the protein level. Methods Expression of MYCN, MYCNOS and ΔMYCN was measured in human NB tissues of different stages. Transcript levels were quantified using a real-time reverse transcriptase polymerase chain reaction assay (QPCR). In addition, relative expression of these three transcripts was compared to the number of MYCN copies, which was determined by genomic real-time PCR (gQPCR). Results Both ΔMYCN and MYCNOS are expressed in all NBs examined. In NBs with MYCN-amplification, these transcripts are significantly higher expressed. The ratio of MYCN:ΔMYCN expression was identical in all tested NBs. This indicates that ΔMYCN and MYCN are co-regulated, which suggests that ΔMYCN is not a regulator of MYCN in NB. However, the ratio of MYCNOS:MYCN expression is directly correlated with NB disease stage (p = 0.007). In the more advanced NB stages and NBs with MYCN-amplification, relatively more MYCNOS is present as compared to MYCN. Expression of the antisense gene MYCNOS might be relevant to the progression of NB, potentially by directly inhibiting MYCN transcription by transcriptional interference at the DNA level. Conclusion The MYCNOS:MYCN-ratio in NBs is significantly correlated with both MYCN-amplification and NB-stage. Our data indicate that in NB, MYCN expression levels might be influenced by MYCNOS but not by ΔMYCN.